The rate of intestinal absorption of natural food folates is not related to the extent of folate conjugation - MCPARTLIN, JOSEPH (American Society for Nutrition, 2006)
Background: Evidence is conflicting as to whether the bioavailability of food folates is influenced by the extent of their conjugation. Objective: The objective was to compare the bioavailability of 3 representative food folate sources with various degrees of glutamylation?ie, egg yolk, spinach, and yeast, whose polyglutamyl folate content measured 0%, 50%, and 100%, respectively. Design: In a randomized crossover trial, 13 male subjects, after a prestudy folate saturation procedure, received in random order either placebo or 500 ?g total folate, which was provided as concentrated freeze-dried extract removed from the normal food matrix of egg yolk, spinach, or yeast. Blood samples (n = 10) were collected before and up to 10 h after treatments, which were administered at weekly intervals. Results: A significant increase from baseline plasma folate concentrations was observed by 0.5 h after treatment with egg yolk folate or spinach folate and by 1 h after treatment with yeast folate, and the concentrations remained significantly elevated for 3?5 h; no plasma folate response was observed after placebo treatment. The overall responses, calculated as plasma folate area under the curve (AUC) for egg yolk, spinach, and yeast folate, were 122.6 ? 23.6, 136.2 ? 21.4, and 102.5 ? 21.1 nmol ? h/L, respectively. No significant differences in AUC were seen between monoglutamyl (egg yolk) folate and either of the polyglutamate-containing folates examined. Conclusion: These results suggest that the ratio of monoglutamate to polyglutamate in natural folates is not a factor that limits the extent of intestinal absorption of food folate.
PUBLISHED
Keywords: Food folate ? polyglutamylation ? plasma folate ? folate bioavailability